Discovery of a new species of Agarista (Ericaceae) in Jalisco, Mexico - González V., Luz María (Instituto de Ecología, A.C., 1989)
Agarista villarraleana, sp. n., from the Sierra Madre del Sur, Jalisco, Mexico, is described. The species is a member  of section Agarista and is easily distinguised from the other species of Agarista know from Mexico because it is a rhizomathous shrub less than 1 m tall with coriaceous leaves and red flowers. It si probably related to A. pulchella Cham. ex G. Don var. pulchella southeastern Brazil.